Property enhancement of dental composite prepared with an isosorbide-based photocurable compound by mixing with TEGDMA. (July 2017) - Shin, Seunghan; Kim, Young-Jae; Toan, Mai; Kim, Jong-Gyu; Nguyen, TanPhat; Ku Cho, Jin
Graphical abstract: Highlights: Isosorbide glycidyl methacrylate (IsoGMA) was synthesized as an analog of BisGMA. IsoGMA resin showed similar mechanical strengths compared to BisGMA/TEGDMA resin. IsoGMA did not have sufficiently high flexural strength by compositing with BaAlSiO2 . Mechanical strengths and water uptake of IsoGMA composite were improved by TEGDMA. Abstract: We synthesized isosorbide glycidyl methacrylate (IsoGMA) as a bio-based analog of bisphenol A-glycidyl methacrylate (BisGMA) and investigated the mechanical and physical properties of IsoGMA-based dental composites to examine the possibility of using IsoGMA as a less-toxic substitute for BisGMA. The dental composites that were prepared with IsoGMA exhibited a low flexural strength compared to that of the BisGMA-based composites due to the high viscosity and surface energy of IsoGMA. After mixing with tri(ethylene glycol) dimethacrylate (TEGDMA), IsoGMA/TEGDMA (8:2) composites exhibited a flexural strength of 120 MPa and a glass transition temperature of 96.9 °C, which were higher than those of the IsoGMA composite (i.e., 79.0 MPa and 65.1 °C, respectively). In addition, TEGDMA improved the water sorption of the IsoGMA composite from 28.0 to 22.2 μg/mm 3, but slightly increased the curing shrinkage from 3.4 to 4.0%.